Bioecological model for the self-control of alcohol consumption and quality of work life - Mendoza, Alejandra Leija; Aguirre, Alicia Álvarez; Zanetti, Ana Carolina Guidorizzi (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2019)
Objective: the purpose of the study was to derive “The Ecology of Human Development” to explain the self-control of alcohol consumption and quality of work life from the nursing approach. Method: analysis and application of the methodology which includes five main steps. Results: bioecological model for self-control of alcohol consumption and quality of life in the workplace. Conclusions: the development of the model can favor identifying and generating fields of action that are useful in the practice of nurses with a scientific basis to prevent or reduce the consumption of alcohol in the workplace.